Pengaruh Kecerdasan Emosional, Kepribadian, Pendidikan Wirausaha dan Motivasi Terhadap Minat Berwirausaha - Nur Ashari, Khoiron; Chandra Kirana , Kusuma (SMARTINDO, 2024)
The purpose of conducting this research is to obtain an explanation of whether there is a relationship betweenemotional intelligence, personality, entrepreneurial education, and motivation towards interest inentrepreneurship among students in Yogyakarta. This research uses a quantitative approach which has numerical data with primary data types. This research uses a questionnaire distributed to active students who live in the Special Region of Yogyakarta in the form of a Google form link. The data collection method used was conveniencesampling where questionnaires were distributed to respondents randomly. Researchers succeeded in collecting130 respondents. Researchers began distributing questionnaires in November 2023. The results of the researchthat has been carried out are that emotional intelligence has a positive effect on interest in entrepreneurship,personality has no effect on interest in entrepreneurship, entrepreneurial education has a positive effect on interest in entrepreneurship, and motivation has a positive effect on interest in entrepreneurship.